Pahlawan dan penghianat dalam sejarah: Analisis peran individu dalam peristiwa sejarah - Sumardin, Oschar; Kabubu, Rusmala Dewi (Rayhan Intermedia, 2025)
Historical events inevitably involve the involvement of many figures who play a role in supporting or opposing the occurrence of an important event. In this study, the analysis aims to reveal the role of individuals in historical events, namely regarding the role of heroes and traitors. This research method uses a descriptive qualitative approach with secondary data collection techniques through literature reviews. Data analysis was conducted by analyzing articles, journals, and books relevant to the research problem. The findings show that in historical records there are figures who are considered